The Claude Bernard and Conrad Waddington Legacy: Homeostasis, When Observed for a Very Long Time, is Homeoresis - Giuliani, Alessandro (Organisms. Journal of Biological Sciences, 2020)
Commentary on: Curtin, P, Austin, C, Curtin, A, Gennings, C, Figueroa-Romero, C, Mikhail, KA et al. 2020, Dysregulated biodynamics in metabolic attractor systems precede the emergence of amyotrophic lateral sclerosis, PLoS Comput Biol, vol. 16, no. 4. e1007773. https://doi.org/10.1371/journal.pcbi.1007773. Citation: Giuliani, A, 2020, “The Claude Bernard and Conrad Waddington Legacy: Homeostasis, When Observed for a Very Long Time, is Homeoresis”, Organisms: Journal of Biological Sciences, vol. 4, no. 1 pp. 15-16. DOI: 10.13133/2532-5876/16958.